A New Age of Theater Architecture - Anisimov, Alexander (project baikal, 2020)
The article considers the reasons of the change in the form-making principles in architecture of entertainment facilities of the late 20th – early 21st centuries: the change in social conditions, development of stage technologies; improvement of engineering equipment of buildings; the shift in evaluation criteria of architectural composition of public buildings and the role of psychology in their perception. The buildings of the recent decades are considered in relation to stage-by-stage changes in the concepts of theatre design of earlier periods. The examples of architecture of entertainment facilities of the new age are provided.